Role of raloxifene in the management of postmenopausal osteoporosis of rheumatoid arthritis patients - Salari M.; Sahebary M.; Sarafraz M.; Asadi Sakhmarresi T. (Sciendo, 2023)
Due to the severe side effects of long-term treatment using hormone replacement therapy, Raloxifene (RLX) is introduced with beneficial effects on rheumatoid arthritis (RA) for postmenopausal women. This review was conducted to collect data from the available literature on RLX for the management of postmenopausal women suffering from RA.